STUDENTS' BEHAVIOUR AND ATTITUDES TO SCHOOL RULES AS OUTCOME OF INVOLVEMENT IN STRUCTURED LEISURE ACTIVITIES - Jankauskiene, Rasa; Sukys, Saulius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the study was to ascertain the associations between students’ participation in extracurricular activities, duration and type of these activities and their antisocial behaviour, attitude towards the rules regulating their behaviour at school and students’ rights. The sample consisted of 1360 (707 males and 653 females) adolescents between ages of 12 and 17 years. The survey-style assessment questionnaire was used in this study. The research revealed that participation in extracurricular activities was associated with more seldom alcohol use, smoking, deviant behaviour at school, and favourable evaluation of school rules. Duration of extracurricular activities a week was not associated with students’ antisocial behaviour. Evaluating substance use and deviant behaviour at school participating in sport students did not differ from those ones who did not participate in any extracurricular activities. Substance use and deviant behaviour at school is less characteristic to those students who attend arts and various activities.